Distributed scheduling of measurements in a sensor network for parameter estimation of spatio-temporal systems - Patan, Maciej (1975- ); Kowalów, Damian (Zielona Góra: Uniwersytet Zielonogórski)
The main aim of the paper is to develop a distributed algorithm for optimal node activation in a sensor network whose measurements are used for parameter estimation of the underlying distributed parameter system. Given a fixed partition of the observation horizon into a finite number of consecutive intervals, the problem under consideration is to optimize the percentage of the total number of observations spent at given sensor nodes in such a way as to maximize the accuracy of system parameter estimates.
Keywords: sensor network; distributed parameter system; parameter estimation; experimental design; sensor scheduling